2017
DOI: 10.3390/ijms18020352
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Syndecan-4 by Organic–Inorganic Hybrid Molecules with a 1,10-Phenanthroline Structure in Cultured Vascular Endothelial Cells

Abstract: Organic–inorganic hybrid molecules constitute analytical tools used in biological systems. Vascular endothelial cells synthesize and secrete proteoglycans, which are macromolecules consisting of a core protein and glycosaminoglycan side chains. Although the expression of endothelial proteoglycans is regulated by several cytokines/growth factors, there may be alternative pathways for proteoglycan synthesis aside from downstream pathways activated by these cytokines/growth factors. Here, we investigated organic–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

8
0

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…We found that the TGF-β signaling regulates the expression of syndecan-4 in vascular endothelial cells (Hara et al, 2016a(Hara et al, , 2016b. Recently, we found that there is an alternative pathway that induces endothelial syndecan-4 expression using 1,10-phenanthroline with or without zinc or rhodium (Hara et al, 2017). Specifically, the syndecan-4 expression can be induced by activation of the hypoxia-inducible factor-1α/β pathway via inhibition of prolyl hydroxylase-domain-containing protein 2.…”
Section: Closing Remarksmentioning
confidence: 99%
“…We found that the TGF-β signaling regulates the expression of syndecan-4 in vascular endothelial cells (Hara et al, 2016a(Hara et al, , 2016b. Recently, we found that there is an alternative pathway that induces endothelial syndecan-4 expression using 1,10-phenanthroline with or without zinc or rhodium (Hara et al, 2017). Specifically, the syndecan-4 expression can be induced by activation of the hypoxia-inducible factor-1α/β pathway via inhibition of prolyl hydroxylase-domain-containing protein 2.…”
Section: Closing Remarksmentioning
confidence: 99%
“…We have also recently found that expression of syndecan-4 (a small heparan sulfate proteoglycan), can be induced through activation of the hypoxia-inducible factor-1α/β pathway via inhibition of prolyl hydroxylase-domain-containing protein 2 in vascular endothelial cells, which is accomplished by using hybrid molecules with a 1,10-phenanthroline structure (Hara et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although regulation of proteoglycan synthesis in vascular endothelial cells can operate in a cell-density-dependent manner (Kaji et al, 2000), little is known about the intracellular signal pathways that mediate cell-density-dependent regulation. Bioorganometallics may be an effective strategy to analyze such pathways as we have previously demonstrated (Hara et al, 2017c(Hara et al, , 2018. Further studies will be required for clarification of the intracellular signal pathways that mediate the regulation of synthesis of perlecan, an essential molecule for the proliferation of vascular endothelial cells (Lord et al, 2014), using organic inorganic hybrid molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The molecules exhibit unique biological activities and can be used to analyze biological systems. We have studied the cytotoxicity of organic-inorganic hybrid molecules (Hara et al, 2019(Hara et al, , 2018Fujie et al, 2019), and have demonstrated the hypoxia-inducible factor-1α/β pathway (Hara et al, 2017c) and the p38 MAPK pathway (Hara et al, 2018) as the intracellular signaling pathways that mediate the synthesis of syndecan-4, a small heparan sulfate proteoglycan, in vascular endothelial cells.…”
Section: Introductionmentioning
confidence: 99%